The Law of Nature and Nurture and Its Impact on Education - Williams, Maureen Chinasa Ola; Ola-Williams, Adeyinka; Ogbaini, Clement Aliu; Fadare, Abigail Oluyemisi (Neraca: Jurnal Pendidikan Ekonomi, 2024)
The debate between nature and nurture is a long-standing and highly deliberated concept in fields ranging from psychology to education. This research therefore sought to determine the effects of nature and nurture on academic performance, learning approaches, behaviours, and educational expectations among students within the context of Ogun State, Nigeria. The study adopted a quantitative research design where data was collected from 240 students and 60 teachers from three local government areas using structured questionnaires. Descriptive statistics, correlation analyses, and independent sample t-tests were used to analyze data. In this context, both direct genetic effects and indirect environmental influences on the investigated educational outcomes were identified. However, the level of using environmental factors including socioeconomic status, family, teaching approaches and resources was higher with significantly more frequency. The correlation analyses and t-tests also corroborated these findings, suggesting a connection between environment and academic performance, learning styles, behavioural patterns and educational achievements. The study adds to the current body of knowledge on the nature-nurture debate within the context of the education system in Nigeria. The findings underscore the role of socioeconomic status in children’s achievement and readiness to learn, emphasizing the need for equal opportunities in education and support for their aspirations. In the same respect, the study emphasizes the importance of a bio-psychosocial model that considers both genetic predeterminations and environmental conditions to explain educational processes and performance.